ANTIBACTERIAL ACTIVITY OF JAVA PREANGER GEL FROM CHERY COFFEE EXTRACT AND GREEN BEAN COFFEE (Coffea arabica L.) AS ANTI-ACNE - Retty Handayani; Hanina Liddini Hanifa; Ariani Nurcahyani (Faculty of Mathematic and Natural Science, Garut University, 2023)
Acne is a skin condition marked by nodules, papules, and pustules. Antibiotic treatment for acne frequently results in resistance. Meanwhile, the usage of various anti-acne medications produces skin irritation. Coffee arabica (Coffea arabica L.) Java preanger has a chlorogenic acid molecule with antibacterial properties against Propionibacterium acnes. This study aimed to examine the antibacterial activity of coffee cherry seed extract and green bean arabica coffee (Coffea arabica L.) Java preanger to determine which had the superior anti-acne action. The gel composition had 2% carbopol and 3%, 6%, and 9% coffee cherry extract concentrations, as well as 5%, 10%, and 15% coffee green bean extract concentrations. The obtained formulations were tested for physical and antibacterial efficacy against Propionibacterium acne. The physical evaluation of the formulations included organoleptic testing, homogeneity, pH, viscosity, spreadability, and antibacterial activity tests. The formulations that met the quality requirements for cherry coffee and coffee green bean gel were selected based on the findings of the physical evaluation. While formula 3 at a concentration of 9% coffee cherry seed extract has the best antibacterial activity with an inhibition of 15.27 mm, green bean coffee at 15% has an inhibition of 17.30 mm.